Reverse Remodeling in Human Heart Failure after Cardiac Resynchronization Therapy Is Associated With Reduced RHO-Kinase Activation - Ocaranza, Maria Paz; Jalil, Jorge E.; Altamirano, Rodrigo; León, Ana de; Moya, Jackeline; Lonis, Alejandra; Gabrielli, Luigi; Nab, Paul Mac; Córdova, Samuel; Paredes, Alejandro; Vergara, Ismael; Bittner, Alex; et al. (Frontiers in Pharmacology, 2021)
Background. A major challenge in heart failure with reduced ejection fraction (HFrEF) is to promote reverse cardiac remodeling. Activation of the Rho kinase (ROCK) signaling pathway in HFrEF patients is associated to myocardial remodeling and LV dysfunction. Cardiac resynchronization therapy (CRT) is effective in patients with HFrRF and left bundle brunch block (LBBB) to promote reverse remodeling and to improve quality of life and survival in this severe condition. The aim was to evaluate the hypothesis that in patients with HFrEF effective CRT reduces ROCK activation. Methods. Prospective study in consecutive patients with HFrHF and LBBB. ROCK activity, measured in peripheral mononuclear cells (PMBCs) as phosphorylation of myosin light chain phosphatase subunit (MYPT1p/t) by Westernblot, was determined before and 3 months after CRT along with echocardiographic parameters of LV systolic function and remodeling. Results. 3 months after CRT, LV ejection fraction improved in 13/28 patients (Responders) by 14,5 % units (p <0.001) whereas in 15 patients it was not modified (Non responders). End systolic diameter was reduced by 16% (p <0.001) in Responders without any change in Non responders. ROCK activation in PBMCs was reduced by 66% in Responders (p <0.05) and it was increased by 10% in non Responders (NS). At baseline there were no significant differences in EF, LV end systolic dimension, neither in ROCK activation between both groups. Baseline LV end diastolic dimension was 5.2 mm larger in the non Responders (p = 0.058) Conclusions. Effective CRT after 3 months, by inducing reverse myocardial remodeling in HFrEF patients significantly decreases ROCK activity in PMBCs. Reduction of ROCK activity in PMBCs could be a marker of reverse cardiac remodeling in patients with heart failure.